Clinicopathological Correlation of Breast Lesions in Pakistani Women: A Prospective Study - Hassan, Masroor; Anjum, Ambreen; Ali, Zahid; Khan, Waseem; Kumar, Gotam; Bashir, Saima (Journal of Neonatal Surgery, 2025)
Objective: To evaluate the clinicopathological correlation of breast lesions among Pakistani women and to determine the relationship between clinical presentation, histopathological findings, and immunohistochemical profiles. Methodology: This prospective study was conducted at the department of Pathology over a one-year period from Feb, 2024 to Feb, 2025. A total of 230 female patients presenting with palpable breast lesions were included using a non-probability consecutive sampling technique. Data were collected through a structured proforma documenting demographic details, clinical features, and pathological findings. Fine needle aspiration cytology (FNAC), excision, or Tru-cut biopsy specimens were processed and stained with hematoxylin and eosin, while immunohistochemistry was performed on malignant cases. Data were analyzed using SPSS version 25, applying descriptive statistics and inferential tests, with a p-value <0.05 considered significant. Results: The mean age of patients was 36.8 ± 11.4 years. Benign lesions (64.8%) predominated, with fibroadenoma being the most frequent (31.3%), followed by fibrocystic disease (17.8%). Malignant lesions accounted for 35.2%, primarily invasive ductal carcinoma (29.1%). Malignant lesions were significantly associated with older age, larger lump size, axillary lymphadenopathy, nipple retraction, and skin changes (p < 0.05). Immunohistochemical analysis showed ER positivity in 60.5%, PR positivity in 55.6%, HER2/neu positivity in 27.2%, and triple-negative phenotype in 17.3%. Conclusion: Benign breast diseases remain more common in Pakistani women; however, invasive ductal carcinoma is the leading malignancy. Clinicopathological correlation remains crucial for timely diagnosis and management, while receptor profiling aids in optimizing individualized therapeutic strategies and improving prognostic outcomes.